Association of creatine kinase elevation with clinical outcomes in chronic myeloid leukemia: a retrospective cohort study. Issue 1 (2nd January 2022) - Bankar, Aniket; Lipton, Jeffrey H.
Abstract: Implications of creatine kinase (CK) elevation, a frequent complication of tyrosine kinase inhibitor (TKI) treatment for chronic myeloid leukemia (CML), on its key treatment outcomes (overall survival (OS) and event-free survival (EFS)), remain unknown. In this single center, retrospective study on 283 chronic phase CML patients on first-line TKI (median follow-up of 8.8 years), 71.7% patients had hyperCKemia with no difference in incidence between imatinib and second generation TKIs (SG-TKIs). In multivariable Cox regression analysis, hyperCKemia was associated with better OS and intermediate- and high-Sokal risk score with worse OS. In multivariable Cox regression for EFS, hyperCKemia and treatment with SG-TKI were associated with improved EFS while intermediate or high Sokal index and higher comorbidities showed worse EFS. Our study provides an evidence on the prognostic value of hyperCKemia in CML and informs clinicians not to change TKI based solely on laboratory elevations of CK.